Poverty to prosperity: Halalpreneures take steps towards economic stability and growth - Nazmi, Nor Asila; Jaiyeoba, Haruna Babatunde (Revon Media Sdn Bhd, 2024)
ENTREPRENEURSHIP is about taking the opportunity to use available resources creatively to influence the market. It can be seen as the ability to create and establish from nothing to something, such as the creation of new enterprises or organisations. Entrepreneurial activity has become one of the tools for individuals who want to create and maintain a sustainable way of life as it not only supports the well-being of individual entrepreneurs but also contributes to the overall well-being of society by generating more job opportunities, driving economic growth and addressing social challenges. As such, entrepreneurship provides the opportunity for people, especially asnaf, to liberate themselves from poverty and take steps towards economic stability and growth. ‘Asnaf’ refers to a group of people worthy of receiving zakat (an annual alms tax or poor rate that each Muslim is expected to pay as a religious duty). This includes the needy, the poor, zakat collectors, the muallaf (converts), the slaves to whom freedom is promised, the debtors, the distant travellers, and those who fight in the name of Allah.